Chinese parents’ intention to vaccinate their 0–5-year-old children with the EV-71 vaccine against hand, foot, and mouth disease and willingness-to-pay - Cheng, Lu; Zhong, Sumei; Xu, Xiaonan; Li, Junrong; Xie, Fangqin; Lin, Yulan; Zhang, Dongjuan (Frontiers in Public Health, 2024)
Background This study aimed to determine the intention and willingness-to-pay (WTP) of Chinese parents/guardians to vaccinate their children with the EV-71 vaccine. Knowledge levels about hand, foot, and mouth disease (HFMD) and the EV-71 vaccine were also investigated. Methods A cross-sectional, self-administered online survey was conducted between November 2022 and March 2023. A stratified multi-stage random sampling method was used to recruit parents/guardians of children aged 0–5 years in southeastern China. Results A total of 3,626 complete responses were received. The mean knowledge score of HFMD was 9.99 (±4.23) out of a total of 14 points. The majority of the participants reported a somewhat willing intent (58.8%), followed by an extremely willing intent (28.9%). Participants who did not consider the EV-71 vaccine expensive (OR = 2.94, 95%CI 2.45–3.53) perceived that the EV-71 vaccine is effective (OR = 2.73, 95%CI 1.52–4.90), and a high knowledge level of HFMD (OR = 1.90, 95%CI 1.57–2.29) had the highest significant odds of having an extremely willing intent to vaccinate their children with the EV-71 vaccine. The median (interquartile range [IQR]) of WTP for the EV-71 vaccine was CNY¥200/USD$28 (IQR CNY¥100-400/USD$14-56). The highest marginal WTP for the vaccine was mainly influenced by the perceived high cost of the vaccine. Those participants who did not consider the EV-71 vaccine expensive had more than 10 times higher odds of vaccinating their children (OR = 10.86, 95%CI 8.49–13.88). Perceived susceptibility, perceived benefits, and perceived barriers were also significant influencing factors in the highest marginal WTP. Conclusion The findings demonstrate the importance of improving health promotion and reducing the barriers to EV-71 vaccination. Therefore, it is important to improve health promotion and reduce the barriers to EV-71 vaccination.